Strategic Planning, Organizational Learning And Villages Own Enterprises Performance : Mediation of Organizational Sustainability - Rizuan Rizuan; Yesi Mutia Basri; Novita Indrawati (Journal of Applied Accounting and Taxation, 2024)
The study analyzes strategic planning, and organizational learning on villages own Enterprises (VOE) performance with organizational sustainability as a mediation. The population in this study was 136 VOE spread throughout Bengkalis Regency. The collection technique used a questionnaire distributed online via Google Forms. Respondents were VOE managers consisting of directors, secretaries, supervisors, and treasurers of VOE. In total, 424 respondents were part of the study. Testing using SEM PLS showed that strategic planning resulted in improved performance and sustainability of VOE organizations in Bengkalis Regency. Organizational learning had an effect on organizational sustainability rather than directly boosting VOE performance.The study's results also proved that organizational sustainability could mediate the impact of strategic planning and organizational learning on the effectiveness of VOE in Bengkalis Regency. This study has practical implications for the importance of good strategic planning and organizational learning to enhance the sustainability and VOE's success. Therefore, it is essential to enhance the skills of VOE managers through training